The performances of circular tube bank fin heat exchangers with fins punched with quadrilateral vortex generators and flow re-distributors. (April 2018) - Dang, Wei; Nugud, Jaafar; Lin, Zhi-Min; Zhang, Yong-Heng; Liu, Song; Wang, Liang-Bi
Highlights: The performances of the fins with vortex generators (VGs) and flow re-distributors (FRs) are investigated. These fins are plane rectangular VGs, curved rectangular VGs, and curved trapezoidal VGs at two cases with/without FRs. The performances of the fin with FRs are higher than its counterparts with VGs only. The area goodness factor of the small fin spacing is larger than that of the large fin spacing. At large Re a the fin with curved trapezoidal VGs and FRs has better performance. Abstract: Air-side heat transfer and flow friction characteristics of six fin patterns for circular tube bank fin heat exchanger are experimentally investigated. These fins are designed regarding that vortex generators could enhance the intensity of secondary flow and decrease the size of the wake region, and the flow re-distributors (FRs) arranged upstream the tube's front stagnation could decrease the dissipation of mechanical energy near the tube regions. The studied fins are the fins punched plane rectangular vortex generators (PRVG fin) with/without FRs, the fin punched curved rectangular vortex generators (CRVG fin) with/ without FRs, the fin punched curved trapezoidal vortex generators (CTVG fin) with/without FRs. The results reveal that: (1) the heat transfer performances of the fins with VGs and FRs are better than their counterpart plain fins; (2) under the same working conditions, the performance of the fins with VGs and FRs are much higher than their counterparts with VGs only; (3) compared to the plain fin, at the same fin pitch the area goodness factor of the large fin spacing is lower than that of the small fin spacing; (4) at small Re a, the area goodness factor of CRVG fin with FRs is slightly higher than that of CTVG fin with FRs or PRVG fin with FRs, while as Re a ranges from 2600 to 5100, CTVG fin with FRs has better heat transfer performance than other fins.